A lithium ion battery negative electrode material binder

By mixing the VAE emulsion with the polyacrylic acid derivative emulsion in a specific proportion, a lithium-ion battery negative electrode material adhesive with both dispersion, adhesiveness and flexibility was prepared, which solved the insufficient performance of the adhesive in the prior art. Problem, improving the overall performance of the battery.

CN116314805BActive Publication Date: 2025-02-18BLUE OCEAN & BLACK STONE TECH CO LTD (FUJIAN)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310249919.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-15
Publication Date
2025-02-18
Estimated Expiration
2043-03-15

AI Technical Summary

Technical Problem

The adhesive of the negative electrode material of lithium-ion battery is difficult to take into account both wetting and dispersibility, adhesion and flexibility, which leads to prone to rupture, cracking or falling off when the electrode is crimped, affecting battery performance.

Method used

The binder of the negative electrode material of lithium-ion battery is prepared by mixing VAE emulsion and polyacrylic acid derivative emulsion at a weight ratio of 40:1-1:10. The binder of the negative electrode material of the binder is improved by blending hydrophilic and hydrophobic properties. and flexibility.

Benefits of technology

The obtained adhesive exhibits good dispersion, adhesion and flexibility during the dispersion and bonding of the negative electrode material of the lithium-ion battery, reducing the AC impedance and improving the first-time Coulomb efficiency of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of adhesives, and specifically provides a binder for negative electrode materials of lithium-ion batteries, which is prepared by mixing VAE emulsion and polyacrylic acid derivative emulsion at a weight ratio of 40:1-1:1; the polyacrylic acid derivative emulsion is obtained by polymerization reaction of hydrophilic acrylic monomer and hydrophobic acrylic monomer at a weight ratio of 3:7-9:1 in an aqueous phase system. The negative electrode material binder of lithium-ion batteries of the present application combines the flexibility of VAE and the dispersibility and adhesion of polyacrylic acid derivatives, and together as a binder for negative electrode materials of lithium-ion batteries, it has good dispersibility, adhesion and flexibility; the button battery assembled with the obtained negative electrode sheet has higher coulomb efficiency and lower AC impedance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of binders, and in particular to a binder for negative electrode materials of lithium-ion batteries. Background Art

[0002] The negative electrode material of lithium-ion batteries is mainly graphite-based materials. Since the surface shape of graphite-based materials is relatively complex and difficult to disperse, higher requirements are placed on the binder. It must have good wetting and dispersion properties on the graphite-based materials, good adhesion to the current collector, and good flexibility to avoid cracking, breaking or falling off when the electrode is curled.

[0003] Therefore, the performance of the binder has a significant impact on the performance of lithium-ion batteries. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a method for preparing a binder for negative electrode materials of lithium ion batteries and a binder for negative electrode materials of lithium ion batteries.

[0005] This application adopts the following technical solutions:

[0006] A binder for negative electrode materials of lithium-ion batteries, prepared by mixing VAE emulsion and polyacrylic acid derivative emulsion in a weight ratio of 40:1-1:10;

[0007] The acrylic acid derivative emulsion is obtained by polymerization reaction of hydrophilic acrylic acid monomer and hydrophobic acrylic acid monomer in a weight ratio of 3:7-9:1 in an aqueous phase system.

[0008] Preferably, the solid content of the lithium ion battery negative electrode material binder is 10-50%.

[0009] Preferably, the solid content of the VAE emulsion is 40-70%.

[0010] Preferably, the weight ratio of the VAE emulsion to the acrylic acid derivative emulsion is 10:1-1:10.

[0011] Preferably, the general chemical formula of the hydrophilic acrylic monomer is CH2=CR 1 R 2 , where R 1 is selected from H or C1-C4 alkyl, R 2Selected from -CONH2, -CONHCH3, -CONHCH2CH3, -CON(CH3)2, -CON(CH2CH3)2, -CONHCH2OH, -CONHCH2CH2OH, -COOCH2CH2OH, -COOCH2CH2CH2OH, -COOCH2CHCH3OH, -COOCH2CH2CH2CH2OH, -COO(CH2CH2O) a H and -COO(CH2) b One or more of PO3H, and / or one or more of organic structures containing -COOH, -COOM, -(C6H5)COOM, -SO3M and -(C6H5)SO3M functional groups, a=1-40, b=1-12, M is selected from Li + 、Na + and K + One or more of the .

[0012] Preferably, the chemical formula of the hydrophobic olefinic acid monomer is CH2=CR 3 R 4 , where R 3 is selected from H or C1-C4 alkyl, R 4 Selected from -COOC n H 2n+1 and -C m H 2m One or more of CN, n=1-40, m=0-6.

[0013] Preferably, the weight ratio of the hydrophilic acrylic monomer to the hydrophobic acrylic monomer is 5:5-9:1.

[0014] Preferably, the polymerization reaction is: adding the hydrophilic acrylic monomer and the hydrophobic acrylic monomer together into a reaction system to carry out a polymerization reaction.

[0015] Preferably, the polymerization reaction is: firstly adding the hydrophilic acrylic monomer into the reaction system for polymerization reaction and then adding the hydrophobic acrylic monomer for polymerization reaction.

[0016] Preferably, the polymerization reaction is: first add 30-70% by weight of the hydrophilic acrylic monomer for polymerization, then add 20-80% by weight of the hydrophobic acrylic monomer for polymerization, then add the remaining hydrophilic acrylic monomer for polymerization, and then add the remaining hydrophobic acrylic monomer.

[0017] In summary, this application has the following beneficial effects:

[0018] The present application adopts a blend of VAE emulsion and a polyacrylic acid derivative emulsion with hydrophilic and hydrophobic properties, which combines the softness of VAE with the dispersibility and adhesion of the polyacrylic acid derivative. The obtained binder is suitable as a binder for lithium-ion battery negative electrode materials and has good dispersibility, adhesion and flexibility. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below.

[0020] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0021] The present application proposes a binder for negative electrode materials of lithium-ion batteries, which is prepared by mixing VAE emulsion and polyacrylic acid derivative emulsion in a weight ratio of 40:1-1:10;

[0022] The polyacrylic acid derivative emulsion is obtained by polymerization reaction of hydrophilic acrylic monomer and hydrophobic acrylic monomer in a weight ratio of 3:7-9:1 in an aqueous phase system.

[0023] VAE emulsion is an emulsion of vinyl acetate / ethylene copolymer. VAE emulsion has good flexibility after film formation. Combined with the high dispersibility and adhesion of polyacrylic acid derivative emulsion, the lithium ion battery negative electrode material binder of the present application has good dispersibility, strong adhesion, good flexibility and suitable electrolyte swelling rate when used for dispersion and bonding of negative electrode materials, thereby being able to reduce AC impedance.

[0024] In a preferred embodiment of the present application, the solid content of the binder of the negative electrode material of the lithium ion battery is 10-50%. In the present application, the solid content test method is: accurately weigh the binder sample in an open weighing bottle, put it in a 120°C oven and bake it for 2 hours, take it out and transfer it to a dryer to cool, and weigh the weighing bottle again. Solid content = (W2-W1) / W0×100%, W0 is the initial weight of the binder sample, W1 is the net weight of the weighing bottle, and W2 is the weight of the weighing bottle after baking.

[0025] In a preferred embodiment of the present application, the solid content of the VAE emulsion is 40-70%. The VAE emulsion usually contains protective colloids such as polyvinyl alcohol and / or surfactants, which can also play a dispersing role on the obtained adhesive. Combined with the hydrophilic and hydrophobic properties of the polyacrylic acid derivative chain segment, the adhesive obtained in the present application has good stability.

[0026] In a preferred embodiment of the present application, the weight ratio of VAE emulsion to polyacrylic acid derivative emulsion is 10:1-1:10. When the weight ratio of VAE emulsion to polyacrylic acid derivative emulsion is within the above range, the comprehensive performance of the adhesive is better. For example, the weight ratio can be 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.

[0027] In a preferred embodiment of the present application, the general chemical formula of the hydrophilic acrylic monomer is CH2=CR 1 R 2 , where R 1 is selected from H or C1-C4 alkyl, R 2 Selected from -CONH2, -CONHCH3, -CONHCH2CH3, -CON(CH3)2, -CON(CH2CH3)2, -CONHCH2OH, -CONHCH2CH2OH, -COOCH2CH2OH, -COOCH2CH2CH2OH, -COOCH2CHCH3OH, -COOCH2CH2CH2CH2OH, -COO(CH2CH2O) a H and -COO(CH2) b One or more of PO3H, and / or one or more of organic structures containing -COOH, -COOM, -(C6H5)COOM, -SO3M and -(C6H5)SO3M functional groups, a=1-40, b=1-12, M is selected from Li + 、Na + and K + For example, the hydrophilic acrylic monomer is acrylamide, hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, N-methylacrylamide, N,N-dimethylacrylamide, acrylic acid, methacrylic acid, sodium acrylate, sodium methacrylate, sodium propylene sulfonate, polyethylene glycol acrylate, etc.

[0028] In a preferred embodiment of the present application, the chemical formula of the hydrophobic olefinic acid monomer is CH2=CR 3 R 4 , where R 3 is selected from H or C1-C4 alkyl, R 4 Selected from -COOC n H 2n+1 and -C m H 2mOne or more of CN, n=1-40, m=0-6. For example, the hydrophobic acrylic monomer can be methyl methacrylate, butyl acrylate, ethyl acrylate, acrylonitrile, octyl acrylate, isooctyl acrylate, 3-butenenitrile, and the like.

[0029] In a preferred embodiment of the present application, the weight ratio of the hydrophilic acrylic monomer to the hydrophobic acrylic monomer is 5:5-9:1. Since VAE is a relatively hydrophobic polymer, the present application adjusts the hydrophilic acrylic monomer to the hydrophobic acrylic monomer so that the hydrophilicity and hydrophobicity of the adhesive are relatively balanced, and the overall performance of the adhesive is better.

[0030] In a preferred embodiment of the present application, the polymerization reaction is: adding a hydrophilic acrylic monomer and a hydrophobic acrylic monomer together into a reaction system for polymerization reaction. The hydrophilic acrylic monomer and the hydrophobic acrylic monomer are added together into a reaction system for polymerization reaction, and the polymer in the obtained polyacrylic acid derivative emulsion is a random copolymer.

[0031] In a preferred embodiment of the present application, the polymerization reaction is: firstly add the hydrophilic acrylic monomer to the reaction system for polymerization reaction and then add the hydrophobic acrylic monomer for polymerization reaction. Firstly add the hydrophilic acrylic monomer to the reaction system for polymerization reaction and then add the hydrophobic acrylic monomer for polymerization reaction, first prepare the hydrophilic acrylic derivative chain segment and then graft the hydrophobic acrylic derivative chain segment, and obtain a similar hydrophilic-hydrophobic block copolymer.

[0032] In a preferred embodiment of the present application, the polymerization reaction is: first add 30-70% by weight of hydrophilic acrylic monomers for polymerization reaction, then add 20-80% by weight of hydrophobic acrylic monomers for polymerization reaction, then add the remaining hydrophilic acrylic monomers for polymerization reaction, and then add the remaining hydrophobic acrylic monomers. First add part of the hydrophilic acrylic monomers and an appropriate amount of initiator, first perform polymerization reaction to form a hydrophilic segment, then add part of the hydrophobic acrylic monomers and an appropriate amount of initiator, the hydrophilic segment is grafted with the hydrophobic segment, then add the remaining hydrophilic acrylic monomers and an appropriate amount of initiator, continue to graft the hydrophilic segment, and finally add the remaining hydrophobic acrylic monomers, continue to graft the hydrophobic segment, and form a similar multi-block copolymer structure of hydrophilic segment-hydrophobic segment-hydrophilic segment-hydrophobic segment, which has better dispersibility for negative electrode materials after mixing with VAE emulsion.

[0033] The technical solution of the present application is described in detail below in conjunction with the embodiments and comparative examples. Unless otherwise specified, the parts in the following embodiments and comparative examples are parts by weight.

[0034] Preparation Example 1

[0035] In a reaction container, 15 parts of acrylamide, 5 parts of hydroxyethyl acrylate, 8 parts of butyl acrylate, 12 parts of methyl acrylate and 130 parts of water were added, the temperature was raised to 65°C, 4 parts of 10wt% ammonium persulfate solution were added dropwise, the reaction system temperature was maintained at 70±2°C, the ammonium persulfate solution was added dropwise within 3 hours, the constant temperature reaction was continued for 2 hours, the temperature was lowered to below 40°C, the pH was adjusted to 6.0-6.5, water was added to adjust the solid content to 20±1%, and a polyacrylic acid derivative emulsion was obtained.

[0036] Preparation Example 2

[0037] In a reaction container, 20 parts of acrylamide, 8 parts of acrylic acid, 6 parts of butyl acrylate, 6 parts of acrylonitrile and 180 parts of water were added, the temperature was raised to 65°C, 4 parts of 10wt% ammonium persulfate solution were added dropwise, the reaction system temperature was maintained at 70±2°C, the ammonium persulfate solution was added dropwise within 3 hours, the constant temperature reaction was continued for 3 hours, the temperature was lowered to below 40°C, the pH was adjusted to 6.0-6.5, water was added to adjust the solid content to 15±1%, and a polyacrylic acid derivative emulsion was obtained.

[0038] Preparation Example 3

[0039] In a reaction container, 20 parts of acrylamide, 8 parts of acrylic acid, 6 parts of hydroxyethyl acrylate, 3 parts of butyl acrylate, 3 parts of acrylonitrile and 200 parts of water were added, the temperature was raised to 65°C, 4 parts of 10wt% ammonium persulfate solution were added dropwise, the reaction system temperature was maintained at 70±2°C, the ammonium persulfate solution was added dropwise within 3 hours, the constant temperature reaction was continued for 3 hours, the temperature was lowered to below 40°C, the pH was adjusted to 6.0-6.5, water was added to adjust the solid content to 15±1%, and a polyacrylic acid derivative emulsion was obtained.

[0040] Preparation Example 4

[0041] In a reaction container, 20 parts of acrylamide, 8 parts of acrylic acid and 100 parts of water are added, the temperature is raised to 65°C, 3 parts of 10wt% ammonium persulfate solution are added dropwise, the reaction system temperature is maintained at 70±2°C, the ammonium persulfate solution is dripped in 2 hours, the constant temperature reaction is continued for 3 hours, 6 parts of butyl acrylate and 6 parts of acrylonitrile are added, 1 part of 10wt% ammonium persulfate solution is added dropwise, the ammonium persulfate solution is dripped in 2 hours, the constant temperature reaction is continued for 3 hours, the temperature is lowered to below 40°C, the pH is adjusted to 6.0-6.5, water is added to adjust the solid content to 25±1%, and a polyacrylic acid derivative emulsion is obtained.

[0042] Preparation Example 5

[0043] 20 parts of acrylamide and 8 parts of acrylic acid are mixed to form a hydrophilic monomer, and 6 parts of butyl acrylate and 6 parts of acrylonitrile are mixed to form a hydrophobic monomer.

[0044] In a reaction container, 14 parts of a hydrophilic monomer and 100 parts of water are added, the temperature is raised to 65° C., 2 parts of a 10wt% ammonium persulfate solution are added dropwise, the temperature of the reaction system is maintained at 70±2° C., the ammonium persulfate solution is dripped off in 2 hours, and the reaction is continued at a constant temperature for 3 hours. Then 6 parts of a hydrophobic monomer are added dropwise, 1 part of a 10wt% ammonium persulfate solution is added dropwise, the ammonium persulfate solution is dripped off in 1 hour, and the reaction is continued at a constant temperature for 3 hours. Then the remaining 14 parts of a hydrophilic monomer are added dropwise, 0.5 parts of a 10wt% ammonium persulfate solution is added dropwise, the ammonium persulfate solution is dripped off in 0.5 hour, and the reaction is continued at a constant temperature for 4 hours. Finally, the remaining 6 parts of a hydrophobic monomer are added dropwise, 0.5 parts of a 10wt% ammonium persulfate solution is added dropwise, the ammonium persulfate solution is dripped off in 0.5 hour, and the reaction is continued at a constant temperature for 5 hours. The temperature is lowered to below 40° C., the pH is adjusted to 6.0-6.5, and water is added to adjust the solid content to 25±1% to obtain a polyacrylic acid derivative emulsion.

[0045] The VAE emulsions in the following Examples 1-5 are derived from Dalian Chemical DA-102, and the VAE emulsions in Examples 6-10 and Comparative Examples 1-4 are derived from Guangwei Chemical GW-706.

[0046] Example 1

[0047] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 1 were mixed at a weight ratio of 10:1, and water was added to adjust the solid content to 20±1% to obtain an adhesive.

[0048] Example 2

[0049] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 2 were mixed at a weight ratio of 3:1, and water was added to adjust the solid content to 20±1% to obtain an adhesive.

[0050] Example 3

[0051] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 3 were mixed at a weight ratio of 1:1, and water was added to adjust the solid content to 20±1% to obtain an adhesive.

[0052] Example 4

[0053] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 4 were mixed at a weight ratio of 1:3, and water was added to adjust the solid content to 20±1% to obtain an adhesive.

[0054] Example 5

[0055] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 5 were mixed at a weight ratio of 1:5, and water was added to adjust the solid content to 20±1% to obtain an adhesive.

[0056] Example 6

[0057] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 1 were mixed at a weight ratio of 1:3, and water was added to adjust the solid content to 20±1% to obtain an adhesive.

[0058] Example 7

[0059] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 2 were mixed at a weight ratio of 1:3, and water was added to adjust the solid content to 20±1% to obtain an adhesive.

[0060] Example 8

[0061] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 3 were mixed at a weight ratio of 1:3, and water was added to adjust the solid content to 20±1% to obtain an adhesive.

[0062] Example 9

[0063] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 4 were mixed at a weight ratio of 1:3, and water was added to adjust the solid content to 20±1% to obtain an adhesive.

[0064] Example 10

[0065] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 5 were mixed at a weight ratio of 1:3, and water was added to adjust the solid content to 20±1% to obtain an adhesive.

[0066] Comparative Example 1

[0067] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 2 were mixed at a weight ratio of 45:1, and water was added to adjust the solid content to 20±1% to obtain an adhesive.

[0068] Comparative Example 2

[0069] The VAE emulsion and the polyacrylic acid derivative emulsion of Preparation Example 2 were mixed at a weight ratio of 1:15, and water was added to adjust the solid content to 15±1% to obtain an adhesive.

[0070] Comparative Example 3

[0071] The adhesive is the polyacrylic acid derivative emulsion of Preparation Example 2, and water is added to adjust the solid content to 15±1%.

[0072] Comparative Example 4

[0073] In Preparation Example 2, acrylamide was adjusted from 20 parts to 5.7 parts, acrylic acid was adjusted from 8 parts to 2.3 parts, butyl acrylate was adjusted from 6 parts to 16 parts, acrylonitrile was adjusted from 6 parts to 16 parts, and the remaining steps remained unchanged. The acrylic acid derivative emulsion was unstable and precipitated after being left for 2 days.

[0074] Negative electrode slurry and electrode preparation

[0075] (1) Mix the binder to be tested with 50% water, disperse at a speed of 3m / s for 12 minutes, then add SP conductive carbon black, stir at a speed of 0.5m / s for 10 minutes, and then stir at a high speed of 6m / s for 120 minutes; reduce the speed to 1m / s, add 50% negative electrode material (Shanshan FSN-1), disperse for 20 minutes, then add the remaining 50% negative electrode material and the remaining 50% water and disperse for 30 minutes, then stir at a high speed of 6m / s for 120 minutes. After dispersion, adjust the viscosity to between 2000-3500mPa·s, and filter with a 150-mesh filter to complete the discharge. Place the copper foil on the coating machine, adjust the scraper scale of the wet film preparation device, evenly pour the filtered slurry, send it into a 100°C environment and bake it in a blast oven until dry, cut it into 12.5cm×5cm specifications and a single-sided surface density of 100-110g / m 2 The pole piece.

[0076] Pole peeling force test: Place the cut pole pieces in a 35% RH constant temperature room for 30 minutes. Place the two pole pieces together with the coating side facing outward and the copper foil side facing inward, and place them in an electric roller press to press the pole pieces to 1.6g / cm 3 After rolling, place it for another 30 minutes. During this period, select five 12.5cm×5cm stainless steel plates, stick double-sided tape of corresponding specifications on the stainless steel plates, and then stick the electrode on the double-sided tape with the coating facing down. Then stick a 2.5cm wide masking tape on the copper foil. Roll the electrode steel plate back and forth with an electric rolling roller at a certain pressure (1kg) for one week, and then use an electronic stripping machine to test the stripping force of the electrode.

[0077] Pole flexibility test: The test was conducted using the ITM-RRD01 softness tester.

[0078] Film electrolyte swelling rate test: The adhesive film to be tested is a film with an average thickness of 100±10μm. Cut a 1×4cm test piece from the film, put it into a 105℃ forced air drying oven for 4 hours, take it out and weigh it and record M1, then put it into a small bottle filled with electrolyte (1M LiPF6 in EC:DMC:EMC=1:1:1) and soak it at a constant temperature for 48 hours, take it out and wipe the electrolyte on the surface of the test piece with filter paper, weigh M2, and the film swelling rate is (M2-M1) / M1×100%.

[0079] The results are shown in Table 1.

[0080] Table 1

[0081] Peel force (N / 5cm) Softness(mN) Electrolyte swelling ratio (%) Example 1 1.87 98 20.2 Example 2 2.27 107 18.4 Example 3 2.40 125 16.7 Example 4 2.65 132 14.8 Example 5 2.78 140 13.7 Example 6 2.51 127 14.5 Example 7 2.57 130 14.1 Example 8 2.60 134 13.3 Example 9 2.62 127 14.8 Example 10 2.65 125 14.6 Comparative Example 1 1.41 94 980.4 Comparative Example 2 2.78 178 8.9 Comparative Example 3 2.81 189 4.3

[0082] It can be seen from the data in Table 1 that the lithium-ion battery negative electrode material binder of the present application is used for the dispersion and bonding of negative electrode materials, and has good performance in peeling force, softness and electrolyte swelling rate, and the performance of acrylic acid derivative emulsion with similar block structure is better than that of acrylic acid derivative emulsion with random structure.

[0083] Button battery assembly process

[0084] The assembly sequence is from bottom to top: negative electrode shell - spring - gasket - lithium sheet - electrolyte - diaphragm - electrolyte - pole piece - positive electrode shell; the battery accessories are assembled in sequence and sealed under 1000kg pressure.

[0085] Electrolyte composition: 1M LiPF6 in EC:DMC:EMC=1:1:1.

[0086] Diaphragm: Celgard 2325.

[0087] Lithium sheet: CROOD 15.0×1.0mm.

[0088] The first coulombic efficiency and impedance data are shown in Table 2.

[0089] Table 2

[0090] First coulombic efficiency / % AC impedance / Ω Example 1 92.3 37.6 Example 2 93.5 35.9 Example 3 94.1 34.2 Example 4 94.4 32.6 Example 5 94.8 36.7 Example 6 94.2 34.7 Example 7 94.6 34.6 Example 8 94.1 33.9 Example 9 94.9 34.1 Example 10 95.0 33.3 Comparative Example 1 77.9 89.3 Comparative Example 2 95.2 53.7 Comparative Example 3 95.5 58.5

[0091] It can be seen from the data in Table 2 that the negative electrode material prepared by the binder prepared in the present application is used in lithium-ion batteries. Due to the characteristics of dispersion, high adhesion, flexibility, etc., the lithium-ion battery has the characteristics of high first coulomb efficiency and low AC impedance.

[0092] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A binder for negative electrode materials of lithium ion batteries, characterized in that: It is made by mixing VAE emulsion and polyacrylic acid derivative emulsion in a weight ratio of 10:1-1:10; The polyacrylic acid derivative emulsion is obtained by polymerization reaction of a hydrophilic acrylic monomer and a hydrophobic acrylic monomer in a weight ratio of 5:5-9:1 in an aqueous phase system; The general chemical formula of the hydrophilic acrylic monomer is CH2=CR 1 R 2 , where R 1 is selected from H or C1-C4 alkyl, R 2 Selected from -CONH2, -CONHCH3, -CONHCH2CH3, -CON(CH3)2, -CON(CH2CH3)2, -CONHCH2OH, -CONHCH2CH2OH, -COOCH2CH2OH, -COOCH2CH2CH2OH, -COOCH2CHCH3OH, -COOCH2CH2CH2CH2OH, -COO(CH2CH2O) a H and -COO(CH2) b One or more of PO3H, and / or one or more of organic structures containing -COOH, -COOM, -(C6H5)COOM, -SO3M and -(C6H5)SO3M functional groups, a=1-40, b=1-12, M is selected from Li + 、Na + and K + One or more of the following; The general chemical formula of the hydrophobic acrylic monomer is CH2=CR 3 R 4 , where R 3 is selected from H or C1-C4 alkyl, R 4 Selected from -COOC n H 2n+1 and -C m H 2m One or more of CN, n=1-40, m=0-6; The polymerization reaction is: first add 30-70% by weight of the hydrophilic acrylic monomer for polymerization reaction, then add 20-80% by weight of the hydrophobic acrylic monomer for polymerization reaction, then add the remaining hydrophilic acrylic monomer for polymerization reaction, and then add the remaining hydrophobic acrylic monomer.

2. The lithium ion battery negative electrode material binder according to claim 1, characterized in that: The solid content of the lithium ion battery negative electrode material binder is 10-50%.

3. The lithium ion battery negative electrode material binder according to claim 1, characterized in that: The solid content of the VAE emulsion is 40-70%.

Citation Information

Patent Citations

  • Waterborne compound adhesive for lithium ion battery

    CN109860597A

  • Adhesive for PVC tablecloth and preparation method thereof

    CN113150722A